Caloric Restriction Is More Efficient than Physical Exercise to Protect from Cisplatin Nephrotoxicity via PPAR-Alpha Activation - Estrela, Gabriel R.; Wasinski, Frederick; Batista, Rogério O.; Hiyane, Meire I.; Felizardo, Raphael J. F.; Cunha, Flavia; de Almeida, Danilo C.; Malheiros, Denise M. A. C.; Câmara, Niels O. S.; Barros, Carlos C.; Bader, Michael; Araujo, Ronaldo C. (Frontiers in Physiology, 2017)
The antineoplastic drug cisplatin promotes renal injury, which limits its use. Protocols that reduce renal cisplatin toxicity will allow higher doses to be used in cisplatin treatment. Here, we compare physical exercise and caloric restriction (CR) as protocols to reduce cisplatin renal injury in mice. Male C57BL/6 were divided into four groups: control, cisplatin, exercise + cisplatin, and 30% CR + cisplatin. Animals were injected with a single dose of cisplatin (20 mg/kg i.p.) and sacrificed 96 h after injection. Quantitative real time PCR, histological analyses, immunohistochemistry, and biochemical measurements were performed to investigate renal injury, necrosis, apoptosis and inflammatory mechanisms. Both protocols protected against cisplatin renal injury, but CR was more effective in reducing uraemia and renal necrosis. The CR+Cisplatin group exhibited reduced serum IL-1β and TNF-α levels. No differences were noted in the renal mRNA expression of cytokines. Both interventions reduced apoptosis, but only the CR+Cisplatin group decreased TNFR2 protein expression. PPAR-α was activated in mice after CR. An antagonist of PPAR-α blocked the protective effect of CR. Both interventions attenuated the nephrotoxicity caused by cisplatin injection, but CR+Cisplatin showed a better response by modulating TNFR2. Moreover, part of the CR benefit depends on PPAR-α activation.